2019
DOI: 10.1007/s41230-019-9029-2
|View full text |Cite
|
Sign up to set email alerts
|

Weibull analysis of fluidity and hardness of ultrasonically degassed secondary Al7Si0.3Mg aluminum alloy

Abstract: I n foundry engineering, casting parameters, such as fluidity and turbulent filling directly affect the properties of the cast metals, i.e. hardness and tensile strength. Predicting these parameters can improve the entire casting process. Also, it is necessary to establish these variables in simulation techniques, and casting procedures, i.e. fluidity test and mechanical test [1]. Dong et al. [2] have investigated the effect of ultrasonic stirring on hardness and concluded that if porosities were not eliminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This analysis can be applied using two equations. The first equation is the Hazen method and the second is Weibull analysis [23,45,46]. These two equations were given below:…”
Section: Resultsmentioning
confidence: 99%
“…This analysis can be applied using two equations. The first equation is the Hazen method and the second is Weibull analysis [23,45,46]. These two equations were given below:…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that minimum porosity was obtained in Al-15Zn-2.5Mg-2.5Cu alloy when 1% AlTi 5 B 1 was used [15] . Yüksel et al [16,17] claimed that as long as the grains are smaller, a porosityfree structure can be achieved. Roy et al [18] claimed that pores were observed around TiB 2 particles.…”
Section: Influence Of Al-b Grain Refiner On Porosity Formation Of Dirmentioning
confidence: 99%